High rate of unplanned pregnancy in the context of integrated family planning and HIV care services in South Africa - Oladele Vincent Adeniyi; Anthony Idowu Ajayi; Mayowa Gabriel Moyaki; Daniel Ter Goon; Gordana Avramovic; John Lambert (BMC, 2018)
Abstract Background Integration of family planning services into HIV care was implemented in South Africa as a core strategy aimed at reducing unintended pregnancies among childbearing women living with HIV. However, it is unclear whether this strategy has made any significant impact at the population level. This paper describes the prevalence and correlates of self-reported unplanned pregnancy among HIV-infected parturient women attending three large maternity centres in the Eastern Cape, South Africa. We also compare unplanned pregnancy rates between HIV-infected parturient women already in care (who have benefitted from services' integration) and newly diagnosed parturient women (who have not benefitted from services' integration). Methods Drawing from the baseline data of the East London Prospective Cohort Study (ELPCS), data of 594 parturient women living with HIV in the Eastern Cape were included. Chi-square statistics and binary logistics regression were employed to determine the correlates of unplanned pregnancy among the cohort. Results The prevalence of unplanned pregnancy was 71% (n = 422) with a higher rate among parturient women newly diagnosed during the index pregnancy (87%). Unplanned pregnancy was significantly associated with younger age, single status, HIV diagnosis at booking, high parity and previous abortion. Women who reported unplanned pregnancy were more likely to book late and have lower CD4 counts. After adjusting for confounding variables, having one child and five to seven children (AOR = 2.2; CI = 1.3-3.1), age less than 21 years (AOR = 3.3; CI = 1.1-9.8), late booking after 27 weeks (AOR = 2.7; CI = 1.5-5.0), not married (AOR = 4.3; CI = 2.7-6.8) and HIV diagnosis at booking (AOR = 3.0; CI = 1.6-5.8) were the significant correlates of unplanned pregnancy in the cohort. Conclusion Unplanned pregnancy remains high overall among parturient women living with HIV in the region, however, with significant reduction among those who were exposed to integrated services. The study confirms that integration of HIV care and family planning services is an important strategy to reduce unplanned pregnancy among women living with HIV. The study's findings have significant implications for the elimination of mother-to-child transmission of HIV in South Africa. Innovative interventions are needed to further consolidate and maximise the benefit of the integration of family planning services with HIV care.